2011
DOI: 10.1074/jbc.m110.199364
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into Human ether-à-go-go-related Gene (hERG) K+ Channel Deactivation Gating from the Solution Structure of the EAG Domain

Abstract: Human ether-à-go-go-related gene (hERG) K+ channels have a critical role in cardiac repolarization. hERG channels close (deactivate) very slowly, and this is vital for regulating the time course and amplitude of repolarizing current during the cardiac action potential. Accelerated deactivation is one mechanism by which inherited mutations cause long QT syndrome and potentially lethal arrhythmias. hERG deactivation is highly dependent upon an intact EAG domain (the first 135 amino acids of the N terminus). Impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
119
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(123 citation statements)
references
References 62 publications
4
119
0
Order By: Relevance
“…The N-terminal N-Cap domains of Kv11.1 channels have been proposed to bind to various regions of the channel protein including the S4S5 linker (36,37) or the cNBH domain (38). Recently, Haitin et al (18) proposed that two charged residues, Arg 7 and Arg 8 , in the N-Cap domain of Kv10.1 channels form a functional interaction with E627R of the cNBH domain.…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal N-Cap domains of Kv11.1 channels have been proposed to bind to various regions of the channel protein including the S4S5 linker (36,37) or the cNBH domain (38). Recently, Haitin et al (18) proposed that two charged residues, Arg 7 and Arg 8 , in the N-Cap domain of Kv10.1 channels form a functional interaction with E627R of the cNBH domain.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to translate our data to real distances because the probability of collision between the cysteine pairs forming disulfide bonds is greatly increased by fluctuations of otherwise flexible structures, even though they are located at a certain distance (40,42,(45)(46)(47). There is evidence that the N-terminal-most segments of the hERG N terminus and the S4-S5 linker constitute highly flexible and/or unstructured regions (28,33,36,39). The protein regions studied here are expected to be dynamically modulated during channel function, so it could be expected that collisions between the cysteine pairs may also be influenced by the molecular rearrangements associated with gating.…”
Section: Herg N-terminal Interactions With the S4-s5 Linkermentioning
confidence: 99%
“…Therefore, it sheds significant new insight into the molecular basis of the protein-protein interactions between the N-terminal distal regions and the S4-S5 linker involved in the control of gating properties and hormonal modulation of hERG (1,2,24,(27)(28)(29)(30)(31)(32)(33)36).…”
Section: Herg N-terminal Interactions With the S4-s5 Linkermentioning
confidence: 99%
“…Subsequent NMR studies from a number of laboratories have shown that the N-Cap contains an amphipathic helix (N-Cap helix, residues 13-23) and a flexible * This work was supported by Grant-in-aid G11S 5829 from the Health Foun-N-terminal tail (N-tail, residues 1-12) (13)(14)(15). More recently, using a construct in which the flexible N-terminal tail was deleted, Morais-Cabral and co-workers (26) showed that the N-Cap helix can fold back and interact with a surface-exposed hydrophobic patch on the remainder of the PAS domain.…”
mentioning
confidence: 99%